Impact of isolated atmospheric aging processes on the cloud condensation nuclei activation of soot particles - F. Friebel (Atmospheric Chemistry and Physics, 2019)
The largest contributors to the uncertainty in assessing the anthropogenic contribution in radiative forcing are the direct and indirect effects of aerosol particles on the Earth's radiative budget. Soot particles are of special interest since their properties can change significantly due to aging processes once they are emitted into the atmosphere. Probably the largest obstacle for the investigation of these processes in the laboratory is the long atmospheric lifetime of 1 week, requiring tailored experiments that cover this time span. This work presents results on the ability of two types of soot, obtained using a miniCAST soot generator, to act as cloud condensation nuclei (CCN) after exposure to atmospherically relevant levels of ozone (O3) and humidity. Aging times of up to 12 h were achieved by successful application of the continuous-flow stirred tank reactor (CSTR) concept while allowing for size selection of particles prior to the aging step. Particles of 100 nm diameter and rich in organic carbon (OC) that were initially CCN inactive showed significant CCN activity at supersaturations (SS) down to 0.3 % after 10 h of exposure to 200 ppb of O3. While this process was not affected by different levels of relative humidity in the range of 5 %–75 %, a high sensitivity towards the ambient/reaction temperature was observed. Soot particles with a lower OC content required an approximately 4-fold longer aging duration to show CCN activity at the same SS. Prior to the slow change in the CCN activity, a rapid increase in the particle diameter was detected which occurred within several minutes. This study highlights the applicability of the CSTR approach for the simulation of atmospheric aging processes, as aging durations beyond 12 h can be achieved in comparably small aerosol chamber volumes (<3 m3). Implementation of our measurement results in a global aerosol-climate model, ECHAM6.3-HAM2.3, showed a statistically significant increase in the regional and global CCN burden and cloud droplet number concentration.